Impact of vaccination on COVID‐19 outcome in multiple sclerosis. (19th July 2022) - Bsteh, Gabriel; Gradl, Christiane; Heschl, Bettina; Hegen, Harald; Di Pauli, Franziska; Assar, Hamid; Leutmezer, Fritz; Traxler, Gerhard; Krajnc, Nik; Zulehner, Gudrun; Hiller, Maria‐Sophia; Rommer, Paulus; et al.
Abstract: Background and purpose: COVID‐19 continues to challenge neurologists in counseling persons with multiple sclerosis (pwMS) regarding disease‐modifying treatment (DMT) and vaccination. The objective here was to characterize predictors of COVID‐19 outcome in pwMS. Methods: We included pwMS with polymerase chain reaction‐confirmed COVID‐19 diagnosis from a nationwide population‐based registry. COVID‐19 outcome was classified as either mild or severe. Impact of DMT, specifically anti‐CD20 monoclonal antibodies (anti‐CD20), and vaccination on COVID‐19 outcome was determined by multivariate models adjusted for a priori risk (determined by a cumulative risk score comprising age, disability, and comorbidities). Results: Of 317 pwMS with COVID‐19 (mean age = 41.8 years [SD = 12.4], 72.9% female, median Expanded Disability Status Scale = 1.5 [range = 0–8.5], 77% on DMT [16% on anti‐CD20]), 92.7% had a mild course and 7.3% a severe course, with 2.2% dying from COVID‐19. Ninety‐seven pwMS (30.6%) were fully vaccinated. After a median 5 months from vaccination to SARS‐CoV‐2 infection (range = 1–9), severe COVID‐19 occurred in 2.1% of fully vaccinated pwMS compared to 9.5% in unvaccinated pwMS ( p = 0.018). A priori risk robustly predicted COVID‐19 severity ( R 2 = 0.605, p < 0.001). Adjusting for a priori risk, anti‐CD20 treatment was associated with increased COVID‐19 severity (odds ratio [OR] = 3.3, R 2 = 0.113, p = 0.003), but exposure to any other DMT was not. Fully vaccinated pwMS showed a significantly decreased risk for severe COVID‐19 (OR = 0.21, R 2 = 0.144, p < 0.001). Conclusions: In a population‐based MS cohort, COVID‐19 course is primarily predicted by a priori risk (depending on age, disability, and comorbidities) explaining about 60% of variance. Anti‐CD20 treatment is associated with a moderately increased risk, whereas reassuringly vaccination provides protection from severe COVID‐19. Abstract : Predictors of COVID‐19 outcome were investigated in 317 patients with multiple sclerosis (pwMS) from a nationwide population‐based registry. A priori risk (determined by a cumulative risk score comprising age, disability, and comorbidities) robustly predicted COVID‐19 severity, explaining about 60% of variance; anti‐CD20 treatment was associated with increased COVID‐19 severity (odds ratio [OR] = 3.3), but exposure to any other disease‐modifying treatment was not. Fully vaccinated pwMS showed a significantly decreased risk for severe COVID‐19 (OR = 0.21).